Real-Time Effort Driven Ventilator Management: A Pilot Study*. Issue 11 (November 2020) - Hotz, Justin C.; Bornstein, Dinnel; Kohler, Kristen; Smith, Erin; Suresh, Anil; Klein, Margaret; Bhalla, Anoopindar; Newth, Christopher J.; Khemani, Robinder G.
Abstract : Objectives: Mechanical ventilation of patients with acute respiratory distress syndrome should balance lung and diaphragm protective principles, which may be difficult to achieve in routine clinical practice. Through a Phase I clinical trial, we sought to determine whether a computerized decision support–based protocol (real-time effort–driven ventilator management) is feasible to implement, results in improved acceptance for lung and diaphragm protective ventilation, and improves clinical outcomes over historical controls. Design: Interventional nonblinded pilot study. Setting: PICU. Patients: Mechanically ventilated children with acute respiratory distress syndrome. Interventions: A computerized decision support tool was tested which prioritized lung-protective management of peak inspiratory pressure–positive end-expiratory pressure, positive end-expiratory pressure/FIO2, and ventilatory rate. Esophageal manometry was used to maintain patient effort in a physiologic range. Protocol acceptance was reported, and enrolled patients were matched 4:1 with respect to age, initial oxygenation index, and percentage of immune compromise to historical control patients for outcome analysis. Measurements and Main Results: Thirty-two patients were included. Acceptance of protocol recommendations was over 75%. One-hundred twenty-eight matched historical controls were used for analysis. Compared with historical controls, patients treated with real-time effort–driven ventilator management received lower peak inspiratory pressure–positive end-expiratory pressure and tidal volume, and higher positive end-expiratory pressure when FIO2 was greater than 0.60. Real-time effort–driven ventilator management was associated with 6 more ventilator-free days, shorter duration until the first spontaneous breathing trial and 3 fewer days on mechanical ventilation among survivors (all p ⩽ 0.05) in comparison with historical controls, while maintaining no difference in the rate of reintubation. Conclusions: A computerized decision support–based protocol prioritizing lung-protective ventilation balanced with reduction of controlled ventilation to maintain physiologic levels of patient effort can be implemented and may be associated with shorter duration of ventilation. Abstract : Supplemental Digital Content is available in the text.